Industry competition and common stock returns - Senarathne, Chamil W.; Long, Wei (Konkurencyjność branży a zwrot z inwestycji w akcje, 2019)
This paper examines the relationship between industry competitiveness and common stock returns of twenty listed firms of the Colombo Stock Exchange. The Herfindahl (1950) H index is extended to include the variance of cross sectional earnings dispersion that accounts for the relative competition of an industry. The regression results show that the industry competitiveness is unrelated to common stock returns when the extended H index is included in the regression specification as a common factor. Although the overall market factor (i.e. market return) remains statistically significant, coefficients of extended H index together with two other controlled factors become statistically insignificant in the regression. These findings suggest that the risk pertaining to industry competition is not priced as it could be diversified away by the appropriately managed value chain of the individual firms and, as such, no compensation for the risk of industry competition is demanded
Management Sciences = Nauki o Zarządzaniu, 2019, vol. 24, no. 3, s. 24-35
Keywords: industry competitiveness; common stock return; campetitive position; value chain innovation; Herfindahl-Hirschman index; konkurencyjność; zwrot z inwestycji w akcje zwykłe; pozycja konkurencyjna; innowacje w łańcuchu wartości; indeks Herfindahla